QUALITY OF SLEEP AND ITS ASSOCIATED FACTORS AMONG DIABETICS AND NON DIABETICS - Kitchlew, Rizwana; Haider, Miqdad; Batool, Sidra; Farooq, Faizan; Shamim Ul Husnain, Muhammad (Journal of Ayub Medical College Abbottabad, 2020)
Background: Diabetes mellitus is the metabolic state which has shown a persistent global rise in numbers. It is therefore necessary to closely assess all aspects of this state. Sleep quality and diabetic control have a relation where both can affect each other. Therefore, we aim to study the quality of sleep and factors affecting it in our diabetic population. The objective of the study was the identification of quality of sleep and factors affecting it in the diabetic and non diabetic adult population. Methods: In this comparative cross sectional study quality of sleep was evaluated in all the patients through the Pittsburgh Sleep Quality Index. Statistical analysis was conducted with the SPSS-23. Results: The total number of study participants were 250 adults (18 years and above), where 125 were diabetics, while 125 were non diabetics. In Diabetic group, the total number of patients with impaired sleep was 65 (52%). In non-diabetic group, impaired sleep was found in 70 (56%) individuals. The mean age of diabetics was 55.2±11.6 years and non-diabetics was 37.23±12.017 years. Prevalence of restless leg syndrome and depression among diabetics was 33 (26.4%) and 30 (24.0%) respectively and in non-diabetic was 20 (16.0%) and 63 (50.4%). Impaired sleep quality was associated with the use of cell phones before going to bed (p-value: 0.01) and watching television until late at night in both groups. Impaired sleep is seen more commonly in uncontrolled DM (RR:1.462 and CI: 0.531 to 4.025) Conclusion: Impaired sleep and uncontrolled DM has a direct relation and the prevalence of Restless leg syndrome (RLS) is higher in Diabetics. Addressing the factors impairing sleep can improve sleep quality and have beneficial effects on the sufferers from this metabolic state. Keywords: Sleep; Diabetes Mellitus; Restless leg syndrome; Depression; Cell phone